2009
DOI: 10.1017/s1368980009990474
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and childhood Mediterranean diet and the development of asthma and allergies in children

Abstract: Objective: To discuss current evidence about the relation between prenatal and childhood Mediterranean diet, and the development of asthma and allergies in children. Design: Review of the literature. Setting and results: Four recent studies conducted in Mediterranean countries (Spain, Greece) and one conducted in Mexico evaluated the association between childhood Mediterranean diet and asthma outcomes in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
56
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 38 publications
(65 reference statements)
6
56
0
3
Order By: Relevance
“…3 In contrast, we did not find any association with a dietary pattern characterized by high intake of fish, vegetables, and fruit 3 whereas adherence to this diet during pregnancy or at school age has been noted to protect against asthma in previous studies. [4][5][6][7][8] Because we did not find a clear association between a dietary pattern including fish and asthmalike symptoms, 3 we hypothesized that any potential beneficial effect of fish consumption in toddlers may be diluted in our previous study as a result of the dietary pattern approach and therefore deserves additional study. Various studies have suggested that early life exposure of n-3 polyunsaturated fatty acids (n-3 PUFA), a major component in fatty fish, protects against the development of asthma.…”
Section: Discussionmentioning
confidence: 86%
“…3 In contrast, we did not find any association with a dietary pattern characterized by high intake of fish, vegetables, and fruit 3 whereas adherence to this diet during pregnancy or at school age has been noted to protect against asthma in previous studies. [4][5][6][7][8] Because we did not find a clear association between a dietary pattern including fish and asthmalike symptoms, 3 we hypothesized that any potential beneficial effect of fish consumption in toddlers may be diluted in our previous study as a result of the dietary pattern approach and therefore deserves additional study. Various studies have suggested that early life exposure of n-3 polyunsaturated fatty acids (n-3 PUFA), a major component in fatty fish, protects against the development of asthma.…”
Section: Discussionmentioning
confidence: 86%
“…Epigenetic or immunologic mechanisms may be implicated because the foods that are introduced during this time deliver the substrates required for the induction of such processes. [23][24][25][26] Fruits and vegetables have been shown to modify immune responses in older children, 19,20 with the proposed mechanism being due to their antioxidant action on inflammatory processes 27 and Treg cells 28 or their action on the gut microflora. 29,30 In addition, we demonstrated a protective effect on food allergy development when cow' s milk protein, in whatever form, was given in the infant' s diet concurrently with breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…A transição à dieta ocidental pode refletir o consumo reduzido em componentes antioxidantes da dieta como vitamina A, carotenóides, vitamina C, vitamina E, zinco, selênio, cobre e compostos bioativos, os quais têm potencial ação protetora no sistema respiratório e na redução da ocorrência de asma 9,10,11 . O padrão dietético ocidental dominante caracteriza-se ainda pelo maior consumo de gorduras saturadas e menor consumo de ácido graxo poli-insaturado ômega 3 (n-3-PUFA), aumentando o risco de ocorrência de asma 9,12,13 . Existem evidências de que a adesão ao padrão Mediterrâneo (composto por peixes, frutas, vegetais, cereais integrais, com alto conteúdo de antioxidantes e n-3-PUFA), tem efeito protetor para a ocorrência da asma 11,13,14 .…”
Section: Introductionunclassified
“…O padrão dietético ocidental dominante caracteriza-se ainda pelo maior consumo de gorduras saturadas e menor consumo de ácido graxo poli-insaturado ômega 3 (n-3-PUFA), aumentando o risco de ocorrência de asma 9,12,13 . Existem evidências de que a adesão ao padrão Mediterrâneo (composto por peixes, frutas, vegetais, cereais integrais, com alto conteúdo de antioxidantes e n-3-PUFA), tem efeito protetor para a ocorrência da asma 11,13,14 .…”
Section: Introductionunclassified